Impact of Tigernuts on Blood Glucose and Insulin Levels in Normal Weight Male Humans - Edokpolor N, Igbinovia; Ohiwerei Wisdom O; Blackie Okosun H; Edebiri Ogbemudia E; Otaye Micheal O; Ohiwerei Faith O (International Journal of Applied and Scientific Research, 2024)
Tigernuts contain bioactive compounds such as sterols, alkaloids, tannins, saponins, resins, and vitamins E and C. This study examined their effects on blood glucose and insulin levels in normal-weight male subjects under resting conditions. Methods: Forty non-habitual tigernut chewers, aged 18–28 years, participated. After recording anthropometric data, subjects rested for 90 minutes. Blood glucose levels were measured using the enzymatic method of Barham and Trinder with a glucometer. Insulin levels were assessed using the ELISA Teco kit following Tiez and Andresen's method. On a separate day, the same subjects consumed 5g of tigernuts as a bolus, followed by 50ml of water. After another 90-minute rest, blood glucose and insulin levels were reassessed. Statistical analysis was conducted using GraphPad Prism Version 8.1. Results: Tigernut consumption led to a slight reduction in blood glucose levels (92.66 ± 2.156 to 89.61 ± 1.907 mg/dl), though not statistically significant. However, insulin levels showed a significant decrease (P<0.05, 4.220 ± 0.297 to 1.705 ± 0.061 µg/ml). Conclusion: Tigernuts demonstrated both blood glucose and insulin-lowering effects in normal-weight male subjects